CDR 2019
DOI: 10.20517/cdr.2019.88
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsies in myeloid malignancies

Abstract: Hematologic malignancies are the most common type of cancer affecting children and young adults, and encompass diseases, such as leukemia, lymphoma, and myeloma, all of which impact blood associated tissues such as the bone marrow, lymphatic system, and blood cells. Clinical diagnostics of these malignancies relies heavily on the use of bone marrow samples, which is painful, debilitating, and not free from risks for leukemia patients. Liquid biopsies are based on minimally invasive assessment of markers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 193 publications
(231 reference statements)
0
9
0
Order By: Relevance
“…Several complex matrices make up the body fluids, especially the peripheral blood, which contains billions of blood cells and different proteins. 17,18 Both require techniques that facilitate remarkably efficient enhancement and robust signal amplification. In order to detect fragile CTCs, a sensitive isolation and release method is required.…”
Section: Introductionmentioning
confidence: 99%
“…Several complex matrices make up the body fluids, especially the peripheral blood, which contains billions of blood cells and different proteins. 17,18 Both require techniques that facilitate remarkably efficient enhancement and robust signal amplification. In order to detect fragile CTCs, a sensitive isolation and release method is required.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of most myeloid neoplasms is based on morphological, immunophenotypic, and molecular characterization of bone marrow (BM) aspirates and biopsies. In addition, MRD monitoring in these neoplasms, with the exception of chronic myeloid leukemia, is currently based on sequential results obtained from BM ( 73 ). Initial studies demonstrated that cfDNA in patients with myeloid neoplasms is higher than in healthy controls, and it can be used as a reliable tool for the identification of genomic abnormalities specific to myeloid neoplasm ( 74 , 75 ).…”
Section: Applications In Hematological Malignanciesmentioning
confidence: 99%
“…At the initial stages of the disease, PB analysis showing a high number of abnormal white blood cells (WBC), or even a very low blood count, can indicate the presence of AML. Hence, the confirmation of the AML diagnosis is performed by further morphologic and cytogenetic assessment in BM aspirates [6,33]. The immunophenotyping by multiparameter flow cytometry (MFC) is conventionally used to accurately diagnose AML based on the identification of intracellular and extracellular markers (e.g., CD13, CD33 and CD34).…”
Section: Diagnosismentioning
confidence: 99%
“…One of the less invasive procedures that have been extensively studied and applied as a complementary method is the PB biopsy, also known as liquid biopsy [6]. This is currently a complementary technique to the gold standard method for the detection of leukemia or MRD because of a smaller number of LSCs in the PB when compared with BM aspirates [34].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation